2017
DOI: 10.1002/ejhf.1114
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of global longitudinal strain in chronic kidney disease: the evidence is building

Abstract: This article refers to 'Prevalence of left ventricular systolic dysfunction in pre-dialysis and dialysis patients with preserved left ventricular ejection fraction' by L.C.R. Hensen et al., published in this issue on pages 560-568.Chronic kidney disease (CKD) is a major health burden affecting roughly 11% of the population with a disproportionally increased propensity to develop cardiovascular disease and events. 1 CKD perpetuates systemic inflammation and oxidative stress, well-known instigators in cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
1
6
1
Order By: Relevance
“…In the present research, GLS was lower in the CKD patient group than in the control group, although no significant difference was determined between the groups in terms of GCS. The majority of previous studies have involved stage 3-5 CKD, and significant decreases in both GLS and GCS have been shown, particularly toward the final stage [3,21,22]. The median GFR in the present study was approx-imately 43 mL/min/1.73 m 2 , and our patients had predominantly stage 3 CKD.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…In the present research, GLS was lower in the CKD patient group than in the control group, although no significant difference was determined between the groups in terms of GCS. The majority of previous studies have involved stage 3-5 CKD, and significant decreases in both GLS and GCS have been shown, particularly toward the final stage [3,21,22]. The median GFR in the present study was approx-imately 43 mL/min/1.73 m 2 , and our patients had predominantly stage 3 CKD.…”
Section: Discussionsupporting
confidence: 50%
“…Numerous similar studies have shown preserved EF in CKD and decreased GLS associated with hospitalization and cardiovascular mortality [3]. Studies have also shown decreased GCS in CKD, although others have reported no difference compared to control groups [3,22]. In the present research, GLS was lower in the CKD patient group than in the control group, although no significant difference was determined between the groups in terms of GCS.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations